Does the use of video improve patient satisfaction in the consent process for local-anaesthetic urological procedures? - Moore, Allison Louise (Department of Surgery, 2021)
Purpose To assess patient satisfaction with the use of Portable Video Media (PVM) for the purpose of taking informed consent for common urological outpatient procedures performed under local anaesthesia. Methods Patients undergoing the following procedures were approached for recruitment: flexible cystoscopy with or without biopsy, transrectal ultrasound-guided prostate biopsy or flexible cystoscopy with insertion or removal of a ureteric stent. Audio-visual media were developed for each procedure, with each script translated from English into isiXhosa and Afrikaans. The study involved a cross-over for each patient between Standard Verbal Consent (SVC) and PVM consent, with each patient randomised to start with SVC or PVM consent. Each of these consent-arms were assessed via a questionnaire. Results 60 patients completed participation, with PVM as the first exposure for 28 patients and 32 patients receiving SVC as their first arm of the study. When comparing the overall satisfaction between SVC and PVM consent (the total scores out of 18 for the questionnaire), patients scored significantly higher for PVM consent (M = 16.3 ± 2.4) compared to SVC (M = 15.4 ± 2.9) (p = 0.002). 92% of the total patient sample preferred PVM consent. Conclusion PVM proved superior to SVC in improving satisfaction in the consent process for common outpatient urological procedures performed under local anaesthesia.